Housing Decisions in Later Life - Leamy, M. author. aut Link
XI, 255 p.
Keywords: This book examines the processes by which older people make housing decisions and the impact such decisions have on the construction of their lives. Evidence is included from a major three-year research study, where older people told stories of their lives. The authors argue that housing decisions are not necessarily the result of rational, analytical and objective thinking. The contribution of other ways of decision-making is often hidden, as when people think intuitively, act impulsively, or for essentially emotional reasons.